2010
DOI: 10.1071/rdv22n1ab342
|View full text |Cite
|
Sign up to set email alerts
|

342 Effects of Melatonin on Preimplantation Development of Porcine Parthenogenetic Embryos

Abstract: In mammalian species, melatonin is a multi-functional pineal gland hormone that regulates several circadian and seasonal rhythms including reproduction. However, the melatonin study was not common as to the oocytes in the pig. Recently, we reported that exogenous melatonin has beneficial effects on nuclear and cytoplasmic maturation during porcine oocyte IVM and we also reported an existence of melatonin receptor on the cumulus cells and granulose cells (Kang JT et al. 2009 J. Pineal Res. 46(1), 22-28). In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Our results confirmed that melatonin supplementation to IVM medium had a potentially significant effect on the degree of bovine cumulus cell expansion, especially at concentrations (10 and 50 ng/ml) proven to be optimal for nuclear maturation. The same promoting effects of melatonin on cumulus cell expansion were reported in porcine oocytes (Kang et al, 2009b). Nevertheless, it is not clear whether this enhancing effect was exerted via its receptors or its direct and indirect antioxidant activities.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our results confirmed that melatonin supplementation to IVM medium had a potentially significant effect on the degree of bovine cumulus cell expansion, especially at concentrations (10 and 50 ng/ml) proven to be optimal for nuclear maturation. The same promoting effects of melatonin on cumulus cell expansion were reported in porcine oocytes (Kang et al, 2009b). Nevertheless, it is not clear whether this enhancing effect was exerted via its receptors or its direct and indirect antioxidant activities.…”
Section: Discussionsupporting
confidence: 72%
“…Nevertheless, it is not clear whether this enhancing effect was exerted via its receptors or its direct and indirect antioxidant activities. As an antioxidant, melatonin might protect cumulus cells against apoptosis (Sugino et al, 2000; Na et al, 2005; Taniguchi et al, 2009; Kang et al, 2009b) and enhance their expansion (Kang et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%